Real Estate Valuation Theory A Critical Appraisal - Mooya, Manya M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This monograph critically reviews and updates real estate valuation theory, which is based on neoclassical economics, in light of developments in heterodox economic theory. Building on a comprehensive historical account of the evolution of value theory, the book uses new institutional economics theory and critical realism as lenses through which problems in standard valuation theory and practice are expatiated, and as the foundation for an alternative theory. The new theory is employed to explain major problems in real estate valuation that are beyond the capability of the standard theory, such as price bubbles in real estate markets, anchoring bias, client influence and valuation under uncertain market conditions.
Preface -- 1 Standard Theory of Real Estate Market Value: Concepts and Problems -- 2 Aristotle to Marshall: The Evolution of Economic Value Theory -- 3 Traditional Valuation Methods -- 4 Automated Valuation Models -- 5 Real Estate Markets and Neoclassical Economic Theory - A Heterodox Critique -- 6 An Alternative Theory of Market Value: Ontological Foundation -- 7 An Alternative Theory: Market Value as Convention and Market Value as Emergence -- 8 Applications to Problems of Theory and Practice -- Postscript.
Keywords: Real estate management; Schools of economics; Economic theory; Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Heterodox Economics; Real Estate Management; Electronic books